Cost savings of EMS administration of bronchodilators and systemic corticosteroids for pediatric asthma patients - Fishe, Jennifer; Garvan, Gerard; Riney, Lauren; Finlay, Erik; Palmer, Sam; Hendry, Phyllis (Frontiers in Public Health, 2025)
BackgroundPediatric asthma costs the United States healthcare system 5 billion annually. A major component of those costs are hospitalizations for acute exacerbations. This brief report examines the cost savings from emergency medical services (EMS) administration of bronchodilators and systemic corticosteroids to pediatric asthma patients, as opposed to waiting for emergency department (ED) arrival.MethodsThis is an economic analysis of data from a study of seven EMS agencies who incorporated both bronchodilators and systemic corticosteroids in their standard operating protocols for all children ages 0–17 years experiencing an asthma exacerbation. Comparing hospital admission rates between children who did and did not receive those medications from EMS, we calculated the number needed to treat (NNT) to prevent one hospitalization, and using the most recently available cost estimate of a pediatric asthma hospitalization, we calculated cost savings for EMS administration of bronchodilators and systemic corticosteroids.ResultsFor all pediatric asthma patients, the NNT was 58.8, which would avert 1,913 hospitalizations nationwide and save 6,886,800. For mild severity exacerbations, the NNT was 9, and for patients with an EMS transport time longer than 40 min, the NNT was 6. If EMS administered bronchodilators and systemic corticosteroids to all mild severity exacerbation and prolonged transport time pediatric asthma patients, then 6,833 mild severity and 500 prolonged transport time patients could avert a hospitalization, resulting in savings of 26,398,800.ConclusionEMS administration of bronchodilators and systemic corticosteroids results in cost savings, most notably for mild severity patients and those with prolonged transport times.